Chemical composition and source-apportionment of sub-micron particles during wintertime over Northern India: New insights on influence of fog-processing. (February 2018) - Rajput, Prashant; Singh, Dharmendra Kumar; Singh, Amit Kumar; Gupta, Tarun
Abstract: A comprehensive study was carried out from central part of Indo-Gangetic Plain (IGP; at Kanpur) to understand abundance, temporal variability, processes (secondary formation and fog-processing) and source-apportionment of PM1 -bound species (PM1 : particulate matter of aerodynamic diameter ≤ 1.0 μm) during wintertime. A total of 50 PM1 samples were collected of which 33 samples represent submicron aerosol characteristics under non-foggy condition whereas 17 samples represent characteristics under thick foggy condition. PM1 mass concentration during non-foggy episodes varied from 24–393 (Avg.: 247) μg m −3, whereas during foggy condition it ranged from 42–243 (Avg.: 107) μg m −3 . With respect to non-foggy condition, the foggy conditions were associated with higher contribution of PM1 -bound organic matter (OM, by 23%). However, lower fractional contribution of SO4 2−, NO3 − and NH4 + during foggy conditions is attributable to wet-scavenging owing to their high affinity to water. Significant influence of fog-processing on organic aerosols composition is also reflected by co-enhancement in OC/EC and WSOC/OC ratio during foggy condition. A reduction by 5% in mineral dust fraction under foggy condition is associated with a parallel decrease in PM1 mass concentration. However, mass fraction of elemental carbon (EC) looks quite similar (≈3% of PM1 ) but the mass absorption efficiency (MAE) of EC is higher by 30% during foggy episodes. Thus, it is evident from this study that fog-processing leads to quite significant enhancement in OM (23%) contribution (and MAE of EC) with nearly equal and parallel decrease in SO4 2−, NO3 − and NH4 + and mineral dust fractions (totaling to 24%). Characteristic features of mineral dust remain similar under foggy and non-foggy conditions; inferred from similar ratios of Fe/Al (≈0.3), Ca/Al (0.35) and Mg/Al (0.22). Positive matrix factorization (PMF) resolves seven sources: biomass burning (19.4%), coal combustion (1.1%), vehicular emission (3%), industrial activities (6.1%), leather tanneries (4%), secondary transformations (46.2%) and mineral dust (20.2%). Graphical abstract: Image 1 Highlights: Foggy episodes were associated with higher OM (by 23%) and MAE of EC (by 30%). Enhanced organonitrates formation in foggy period is revealed from secondary WSON. PMF resolved 7 sources with predominant contribution of secondary aerosols (46.2%). Abstract : In this study, fog-processing enhanced organic matter contribution by 23%, MAE of EC by 30% and WSON/TN by 20%.